Optimalisasi Penugasan Kerja dan Distribusi Roti dengan Metode Assignment dan Spanning Tree - Wahyudin; Satya, Egar Naufal Ari; Ramadan, Riki (Jurnal Sistem Teknik Industri, 2021)
A company is required to perform activities effectively and efficiently, employee assignment problems must be done optimally, the high element of subjectivity will cause miscommunication between employees to distribute an item. This research was conducted on UMKM bakers who have not optimized the problem of employee assignment and distribution process. With this research is expected to increase corporate competition. Then the researchers used the Penalty method to allocate employees to obtain optimal results and networking methods to solve distribution problems. Data obtained from the observation results will be tested according to the method used. After the results are obtained manually the results are then compared with lingo and POM-QM software programs. The results of the research assignment were Andik distributing bread to Karang Indah, Budiman distributing bread to Jatirasa, Saepul distributing bread to Karang Pawitan, Indra distributing bread to Nagasari, Maman distributing bread to Kepuh, Aep distributing bread to Johar, and Jamhari distributing bread to Cinangoh. Total sales of 1039 pieces of bread. The distribution network results from the research are Companies – Nagasari, Companies – Jatirasa, Jatirasa – Karang Indah, Nagasari – Johar, Karang Indah – Karang Pawitan, Karang Pawitan – Kepuh, Johar – Cinangoh. The total distance traveled is 7550 m.